Электоральные процессы в России: вопросы противодействия коррупции - Zagumennikova I. V., Plotnikova A. V. (Инновационные технологии в науке и образовании, 2016)
The article deals with the problem of corruption in the aspect of the forthcoming elections to the State Duma, as well as measures to be taken by the state, if not aimed at eliminating, or at least to minimize corruption in the electoral field.
Keywords: коррупция; власть; закон; Россия; ответственность; бизнес; избирательный процесс; Russia; business; corruption; power; Responsibility; law; электоральные процессы; electoral processes; the electoral process